Customized optimization of lignocellulolytic enzyme cocktails for efficient conversion of pectin-rich biomass residues. (1st December 2022) - Gao, Liwei; Liu, Guodong; Zhao, Qinqin; Xiao, Ziyang; Sun, Wan; Hao, Xianwei; Liu, Xinmin; Zhang, Zhongfeng; Zhang, Peng
Abstract: Pectin is a major component in many agricultural feedstocks. Despite the wide use in industrial production of cellulases and hemicellulases, the fungus Trichoderma reesei lacks a complete enzyme set for pectin degradation. In this study, three representative pectinolytic enzymes were expressed and screened for their abilities to improve the efficiency of T. reesei enzymes on the conversion of different agricultural residues. By replacing 5 % of the T. reesei proteins, endopolygalacturonase and pectin lyase remarkably increased the release of sugars from inferior tobacco leaves. In contrast, pectin methylesterase showed the strongest improving effect (by 31.1 %) on the hydrolysis of beetroot residue. The pectin in beetroot residue was only mildly degraded with the supplementation of pectin methylesterase, which allowed the extraction of pectin keeping the original emulsifying activity with a 51.1 % higher yield. The results provide a basis for precise optimization of lignocellulolytic enzyme systems for targeted valorization of pectin-rich agricultural residues. Graphical abstract: Unlabelled Image